Scientific-theoretical principles of the functioning insurance and funded pension system models - L. Khachumova (Модернизация, инновация, развитие, 2016)
Retracted articleThe main value of the pension system in the world is to improve the living standards of citizens in old age, and income replacement by smoothing consumption function. The article reveals the scien tific and theoretical apparatus and operation of the insurance models and funded pension system at the country level.